Changes in sexual function in women undergoing posterior colporrhaphy & perineorrhaphy with or without anterior colporrhaphy - Alhaizan, Maysoon; Almandeel, Hazem; Alhainiah, Maha; Aldabeeb, Dana; Bogis, Abdulrahman; Alshaikh, Ghadeer (Journal of the Pakistan Medical Association, 2026)
Objective: To assess the effects of posterior colporrhaphy and perineorrhaphy on women’s sexual function. Method: The prospective, observational study was conducted at King Saud University Medical City, Riyadh, Saudi Arabia, between December 2022 and August 2023, and comprised women scheduled for surgery after having been diagnosed with posterior vaginal or a combination of posterior and anterior vaginal prolapse. Data was collected using the Arabic version of the Pelvic Organ Prolapse/Incontinence Sexual Questionnaire before surgery and six months post-surgery. Data was analysed using SPSS 26. Results: Of the 40 women, 17(42.5%) were aged 36-45 years and 5(12.5%) were aged <55 years. Overall, 24(60%) women underwent posterior colporrhaphy combined with perineorrhaphy, while 16(40%) had both posterior and anterior colporrhaphy along with perineorrhaphy. With respect to Pelvic Organ Prolapse/Incontinence Sexual Questionnaire score, 3(7.5%) patients saw a drop after surgery, 27(67.5%) experienced an increase of <1, and 10(25%) had an improvement >1. The average difference in the scores post-surgery was 0.67±0.42. Significant improvements were noted in all domains (p<0.05) after pelvic organ prolapse repair. Conclusion: Women showed significant enhancement in sexual function after receiving either posterior pelvic organ prolapse repair or a combination of posterior and anterior repair. Key Words: Pelvic organ prolapse, Sexual dysfunction, Colporrhaphy, Perineorrhaphy, Quality of life.